2020
DOI: 10.1093/ehjci/jeaa003
|View full text |Cite
|
Sign up to set email alerts
|

Acute redistribution of regional left ventricular work by cardiac resynchronization therapy determines long-term remodelling

Abstract: Aims  Investigating the acute impact of cardiac resynchronization therapy (CRT) on regional myocardial work distribution in the left ventricle (LV) and to which extent it is related to long-term reverse remodelling. Methods and results  One hundred and thirty heart failure patients, referred for CRT implantation, were recruited in our prospective multicentre study. Regional myocardial work was calculated from non-invasive seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
4
27
0
2
Order By: Relevance
“…Prior to LBBAP, patients had inefficient septal function with markedly low MWE (35.3 ± 17.8%) and high WW (607.1 ± 276.5 mmHg%) compared with global LV (GWE:64.6 ± 7.8%;GWW: 410.3 ± 166.6 mmHg%).Regional analysis of MW revealed that LBBAP leads to significant MWE increases (from 35.3 ± 17.8 to 69.6 ± 19.0%, P = 0.001) and WW reductions (from 607.1 ± 276.5 to 330.8 ± 254.3 mmHg%, < 0.001) in the septum, indicating major improvement in LV function. Reducing septal-lateral work differences in the LV is an important determinant of reverse remodeling after CRT implantation ( 28 , 30 , 31 ). This study showed that LBBAP could reduce the regional differences in myocardial performance between the septal and lateral segments, which leads to more homogeneous regional MW distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to LBBAP, patients had inefficient septal function with markedly low MWE (35.3 ± 17.8%) and high WW (607.1 ± 276.5 mmHg%) compared with global LV (GWE:64.6 ± 7.8%;GWW: 410.3 ± 166.6 mmHg%).Regional analysis of MW revealed that LBBAP leads to significant MWE increases (from 35.3 ± 17.8 to 69.6 ± 19.0%, P = 0.001) and WW reductions (from 607.1 ± 276.5 to 330.8 ± 254.3 mmHg%, < 0.001) in the septum, indicating major improvement in LV function. Reducing septal-lateral work differences in the LV is an important determinant of reverse remodeling after CRT implantation ( 28 , 30 , 31 ). This study showed that LBBAP could reduce the regional differences in myocardial performance between the septal and lateral segments, which leads to more homogeneous regional MW distribution.…”
Section: Discussionmentioning
confidence: 99%
“…paradoxical) work [ 31 ]. Recently, Duchenne et al demonstrated that acute redistribution of regional LV work, specifically from the lateral wall towards the septum, determined long-term reverse remodelling [ 32 ]. With regional systolic strain representing the main determinant of regional myocardial work in that study, redistribution of work through reversal of wasted work was based on reversal of septal paradoxical stretch also in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The dyssynchronous ventricular septum produces large amounts of wasted work, and consequently, after response to this treatment, WW reduces and global work index and LV performance increases [8]. A recent study showed that there is acute redistribution of segmental work between septal and lateral work, which is a strong determinant of LV reverse remodeling [28].…”
Section: Cardiac Dyssynchronymentioning
confidence: 99%